The Importance of Family Support on the Desistance of the Ex-convicts Discharged from Prison - Seyidoglu, Sadullah; Kizmaz, Zahir (Istanbul Univ, 2024)
This study concentrates on the impact of socioeconomic and psychological support from the families of ex-convicts discharged from prison on their desistance from crime, both in prison and in the post-prison period. A qualitative research method was adopted in this study. In this context, 50 ex-convicts who had not committed a crime since at least two years after their release from prison were interviewed. The ex-convicts interviewed were selected from among the individuals residing in Diyarbakr. In the conducted research, the majority of the participants stated that the support they were provided by their families both in prison and in the post-prison period made a significant contribution to their desistance from crime. In this context, it was concluded that being visited by the families of ex-convicts while they were in prison, making phone calls, meeting their pecuniary needs in prison, and continuing to provide socio-economic support by the family in the post-prison period were effective in reducing their desistance from crime. In addition, it was determined that ex-convicts who were married and had children committed crime more easily. In conclusion, it was presented in this study that the family relations of ex-convicts discharged from prison continued, that an exclusionary attitude towards them was avoided, and that income and accommodation support was provided. Thus, this attitude had a significant role in ex-convicts' quitting their crime. Based on these findings, it was concluded that it is necessary to provide family-based support programmes and activities more systematically to prevent ex-convicts from recommitting crime.
Keywords: Ex-convicts; ex-convicts' desistances from crime; the effect of family on x-convicts' desistances from crime